2022
DOI: 10.3389/fonc.2022.815917
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Safety of Toripalimab Combination Therapies for Patients With Chemo-Resistant Choriocarcinoma

Abstract: Toripalimab as a novel PD-1 inhibitor has presented its promising efficacy in patients who developed chemo-refractory carcinomas, whereas no study has ever investigated the effectiveness of toripalimab in chemo-resistant choriocarcinoma. Here we reported the effectiveness and safety data of 4 patients with chemo-resistant choriocarcinoma who underwent PD-1 antibody therapy by toripalimab and individualized chemotherapies. From January 2019 to August 2020, 4 patients with choriocarcinoma were admitted in Shengj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Favorable outcomes, including complete responses, were observed in cases with strong PD-L1 expression (often 90%-100%) (37)(38)(39)(40)(41)(42)(43). Additionally, toripalimab and tirelizumab showed promise in chemo-resistant choriocarcinoma (44,45).In a phase 2 clinical trial, the combination of camrelizumab and apatinib showed potential for chemo-resistant choriocarcinoma, with a 50% complete response rate (46). In the TROPHIMMUN trial, avelumab also demonstrated curative potential in 50% chemotherapy-resistant gestational trophoblastic tumors, including cases of choriocarcinoma (47).…”
Section: Discussionmentioning
confidence: 99%
“…Favorable outcomes, including complete responses, were observed in cases with strong PD-L1 expression (often 90%-100%) (37)(38)(39)(40)(41)(42)(43). Additionally, toripalimab and tirelizumab showed promise in chemo-resistant choriocarcinoma (44,45).In a phase 2 clinical trial, the combination of camrelizumab and apatinib showed potential for chemo-resistant choriocarcinoma, with a 50% complete response rate (46). In the TROPHIMMUN trial, avelumab also demonstrated curative potential in 50% chemotherapy-resistant gestational trophoblastic tumors, including cases of choriocarcinoma (47).…”
Section: Discussionmentioning
confidence: 99%
“…Etoposide, carboplatin, bleomycin, and methotrexate are examples of common chemotherapy drugs ( 3 , 6 ). Furthermore, patients with choriocarcinoma who are resistant to chemotherapeutic drugs can be treated with a combination of toripalizumab and surgery ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al [ 22 ] reported a series of 4 patients with multidrug resistant disease who were all treated with the anti-PD-1 agent toripalimab ( Table 1 ). Toripalimab was not given as monotherapy but combined with chemotherapy in all 4 patients (1 patient received nab-paclitaxel and bevacizumab with toripalimab, the other 3 patients paclitaxel and cisplatin).…”
Section: Immunotherapy For Patients With High-risk Chemotherapy Insen...mentioning
confidence: 99%
“…The majority are case reports or small series of patients with multidrug resistant GTN, but evidence for the use of CPIs in an earlier setting, e.g., low-risk disease resistant to singleagent chemotherapy, is emerging [21]. Most patients have been treated with pembrolizumab, but other anti-PD1 agents have been successfully used [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation